2021
DOI: 10.1073/pnas.2101160118
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-five years later: Long-term effects of the Matlab maternal and child health/family planning program on older women’s well-being

Abstract: Family planning programs are believed to have substantial long-term benefits for women’s health and well-being, yet few studies have established either extent or direction of long-term effects. The Matlab, Bangladesh, maternal and child health/family planning (MCH/FP) program afforded a 12-y period of well-documented differential access to services. We evaluate its impacts on women’s lifetime fertility, adult health, and economic outcomes 35 y after program initiation. We followed 1,820 women who were of repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The study area was the site for the Maternal Child Health/Family Planning (MCH/FP) Program that was initiated in Matlab in 1977 by the International Center for Diarrheal Disease Research, Bangladesh (icddr,b). This program has had notable positive effects on women's health in the area, including substantial changes in lifetime contraceptive use and fertility behaviors [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study area was the site for the Maternal Child Health/Family Planning (MCH/FP) Program that was initiated in Matlab in 1977 by the International Center for Diarrheal Disease Research, Bangladesh (icddr,b). This program has had notable positive effects on women's health in the area, including substantial changes in lifetime contraceptive use and fertility behaviors [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study sample was identified using the Matlab Health and Demographic Surveillance System (MHDSS), which is a unique longitudinal demographic registration system that has recorded all births, deaths, marriages, and migrations occurring in the area since 1974. The first Matlab Health and Socioeconomic Survey sampled 7% of households included in the MHDSS in 1996 (MHSS1) [ 41 ]. This study primarily used MHSS2, which was a panel follow-up of MHSS1 conducted from 2012 to 2014.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, much of the existing FP modeling landscape has focused on macro- or population-level dynamics of family planning, with far less attention paid to individual needs and preferences (Brunson 2020; Speizer, Bremner, and Farid 2022) or individual-level consequences (Barham et al 2021; Brunson and Suh 2020; Finlay and Lee 2018; Okenwa, Lawoko, and Jansson 2011; Schwarz et al 2019). Due to the individual nature of the biological and behavioral underpinnings of family planning and its consequences, deeper understanding of how family planning is intertwined with individuals’ lives and health at the micro -level can contribute to more effective, person-centered design of both contraceptive technologies and programmatic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Among these data sets, MHPD is unique in several contexts (Table 2): (i) The MHPD has been tracking the rural households of the country for a period of over three decades , (ii) it has already been used in more than 70 academic studies which might have enhanced the government, non-governmental, and international development policies since the late 1980s (Hossain 2002;Hossain and Bose 2004;IMF 2005;World Bank 2012;Madhur and Faruqee 2016;Hossain, Kairy, and Bayes 2016); and (iii) In terms of content, while all three studies have many common dimensions of a standard LSMS, the MHPD has been collecting more detailed time use of households' earning members and a detailed account of the costs and returns of a parcel of land that the respondent could remember the best. In addition to those nationally representative panel studies, there is a unique and rich longitudinal demographic study on births, deaths, marriages, and migrations in small Upazila, Matlab, in Bangladesh (Barham et al 2021). 1957/58, 1963/64, 1974/5, 1983/4, 1993, 2008-10 • 1989, 1991, 1993, 1997, 2000, 2004, 2006, 2009 The MHPD was maintained by the late Dr. Mahabub Hossain, a well-known agriculture and development economist who worked with several reputed organizations in Bangladesh and other regions.…”
Section: Introductionmentioning
confidence: 99%